Structural and photoluminescence investigation on the hot-wire assisted plasma enhanced chemical vapor deposition growth silicon nanowires - Chong, Su Kong; Goh, Boon Tong; Wong, Yuen Yee; Nguyen, Hong Quan; Do, Hien; Ahmad, Ishaq; Aspanut, Zarina; Muhamad, Muhamad Rasat; Dee, Chang Fu; Rahman, Saadah Abdul (Elsevier, 2012)
High density of silicon nanowires (SiNWs) were synthesized by a hot-wire assisted plasma enhanced chemical vapor deposition technique. The structural and optical properties of the as-grown SiNWs prepared at different rf power of 40 and 80 W were analyzed in this study. The SiNWs prepared at rf power of 40 W exhibited highly crystalline structure with a high crystal volume fraction. X-C of similar to 82 and are surrounded by a thin layer of SiOx. The NWs show high absorption in the high energy region (E > 1.8 eV) and strong photoluminescence at 1.73 to 2.05 eV (red-orange region) with a weak shoulder at 1.65 to 1.73 eV (near IR region). An increase in rf power to 80 W reduced the X-C to similar to 65 and led to the formation of nanocrystalline Si structures with a crystallite size of < 4 nm within the SiNWs. These NWs are covered by a mixture of uncatalyzed amorphous Si layer. The SiNWs prepared at 80 W exhibited a high optical absorption ability above 99 in the broadband range between 220 and similar to 1500 nm and red emission between 1.65 and 1.95 eV. The interesting light absorption and photoluminescence properties from both SiNWs are discussed in the text. (C) 2012 Elsevier B.V. All rights reserved.